2014
DOI: 10.4085/1062-6050-49.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Sport-Related Concussion and Sensory Function in Young Adults

Abstract: These results suggest that concussion history has a negative effect on visual processing in young adults. Further, upper-level neurocognitive deficits associated with concussion may, in part, result from less efficient downstream sensory capture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 51 publications
3
34
0
Order By: Relevance
“…task relative to sub-concussed or control athletes (Moore, Broglio, & Hillman, 2014;Moore, Lepine, & Ellemberg, 2017). Taken together, these results suggest that concussions could affect early evoked potentials.…”
Section: Introductionsupporting
confidence: 50%
“…task relative to sub-concussed or control athletes (Moore, Broglio, & Hillman, 2014;Moore, Lepine, & Ellemberg, 2017). Taken together, these results suggest that concussions could affect early evoked potentials.…”
Section: Introductionsupporting
confidence: 50%
“…Similar findings related to persistent changes in the P3a component have been reported in previously concussed participants 22 to 60 months [60], 3.4 years [8], and 26 years [15] post-injury. To a lesser extent, suppressed Ne has been shown at 2.9 years [47], suppressed P1 amplitude at 6.7 years [45], and an altered N2 component at 7.1 years post-injury [46]. While these findings were generated in response to the target stimuli during a visual task, compared to the auditory task implemented here, it is possible that ongoing deficits may need to be accounted for by clinicians when interpreting post-concussion results.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, by eliminating upper body injuries from the analysis, we eliminated the chance of a concussion being misclassified as an upper body orthopaedic injury. Lower body injuries are the most common musculoskeletal injuries in ice hockey, 13 so limiting the orthopaedic injury group to lower body injuries made that group more homogeneous while it continued to represent NHL orthopaedic injuries. Finally, classifying a concussive injury as an upper body injury may result in underreporting 31 or missing these injuries, which would also limit our ability to assess all concussive injuries.…”
Section: Limitationsmentioning
confidence: 99%
“…7 In general, recovery to preinjury levels of functioning is spontaneous, with symptom resolution within days to weeks postinjury. 8 However, authors of recent laboratory studies have indicated that subtle deficits persisted in measures of gait and balance, 9 dynamic motor tasks, 10 working memory, 11 reaction time, 12 visual processing, 13 and cognition, 14 even after concussion-related symptoms resolved.…”
mentioning
confidence: 99%
See 1 more Smart Citation